Terapi Realitas Pada Remaja untuk Memahami Masalah Diri Di Panti Asuhan Wiloso Projo Yogyakarta - Espransa, Vera Bella (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2025)
Adolescence is a stage in which individuals experience various changes within themselves. These changes result in emotional uncertainty, attitudes, and responsibility, especially for adolescents living in orphanages with limited family roles. Therefore, efforts are needed to understand adolescents' self-discipline, such as through reality therapy. The purpose of this study was to apply reality therapy to adolescents at the Wiloso Projo orphanage in Yogyakarta. This intervention aims to increase self-confidence, encourage independence, and strengthen adolescents' social interactions. The research method used a qualitative approach with data collection techniques using interviews, observation, and literature studies. Data analysis focused on data reduction, presentation, and verification. The results showed that adolescents have their own unique problem characteristics that they can identify and analyze independently. Adolescents can recognize the forms of hopes and goals they want to change as a response to understanding themselves. Thus, through reality therapy, adolescent participants can understand their own problems and strive to make changes. This study contributes to the application of reality therapy to adolescents in orphanages and has had a fairly effective impact on understanding their problems